Effect of Heavy Ion Irradiation Dosage on the Hardness of SA508-IV Reactor Pressure Vessel Steel - Xue Bai; Sujun Wu; Peter K. Liaw; Lin Shao; Jonathan Gigax (Metals, 2017)
Specimens of the SA508-IV reactor pressure vessel (RPV) steel, containing 3.26 wt. % Ni and just 0.041 wt. % Cu, were irradiated at 290 °C to different displacement per atom (dpa) with 3.5 MeV Fe ions (Fe2+). Microstructure observation and nano-indentation hardness measurements were carried out. The Continuous Stiffness Measurement (CSM) of nano-indentation was used to obtain the indentation depth profile of nano-hardness. The curves showed a maximum nano-hardness and a plateau damage near the surface of the irradiated samples, attributed to different hardening mechanisms. The Nix-Gao model was employed to analyze the nano-indentation test results. It was found that the curves of nano-hardness versus the reciprocal of indentation depth are bilinear. The nano-hardness value corresponding to the inflection point of the bilinear curve may be used as a parameter to describe the ion irradiation effect. The obvious entanglement of the dislocations was observed in the 30 dpa sample. The maximum nano-hardness values show a good linear relationship with the square root of the dpa.